Electronic structure evolution from metallic vanadium to metallic VxOy: a nappes study for o2+v gas-solid interaction - Ranjan, Ravi; Mhamane, Nitin B.; Kolekar, Sadhu K.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2022)
Gas-solid interactions between molecular oxygen and metallic vanadium surfaces and the systematic evolution in the electronic structure of vanadium oxide (VOx) surfaces have been explored in the present work by near-ambient pressure photo-electron spectroscopy (NAPPES). The current article studies the evolution of various oxides of vanadium as a function of partial pressure of O2 (ultrahigh vacuum to 1 mbar), temperature (298- 875 K), and the exposure time to oxygen (up to 18 h). Valence -band (VB) and core-level spectral measurements recorded with UV (He-I = 21.2 eV) and Al K alpha (1486.6 eV) photons, respectively, show interesting changes. (1) Oxidation is limited to the top layers of vanadium at 298 K and up to a partial pressure of 1 mbar O2. About 50% of vanadium gets oxidized, and the remaining amount exists as metal within the top 10 nm. (2) Metallic vanadium disappears above 625 K, and it is predominantly oxidized to a mixture of V4+ and V5+ oxidation states at a 0.1 mbar partial pressure of O2. Points 1 and 2 suggest the predominantly thermodynamically controlled nature of vanadium oxidation through oxygen diffusion into the subsurface and bulk layers. (3) The Fermi-level (EF) feature observed first at >= 725 K at a 0.1 mbar O2 pressure demonstrates the formation of metallic VO2; however, its metallic nature is preserved even at ambient temperature due to interweaving nanodomains of VOx with VO2. (4) Only partial conversion of surface layers to V5+ (V2O5) along with VO2 and V2O3 (within the probing depth of 8-10 nm by near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS)) was observed even after prolonged heating (18 h) in 1 mbar O2 pressure. (5) The nature of the surface changes between metal and semiconducting/ insulator oxides is substantiated by the observation of changes in work function (phi) and EF features. Typical VB features and Fermi intensity of V-metal and vanadium oxides were observed, and the results were corroborated with core-level and VB spectra. The present results extend the capabilities of NAPPES to explore the electronic structure evolution as a function of reaction conditions and underscore its relevance to areas such as heterogeneous catalysis and sensing.

Enhanced field emission behaviour from ethylene glycol mediated synthesis of 2D hexagonal SnS2 disc with nanoparticle - Mutadak, Pallavi R.; Chaudhari, Nilima S.; Gadhave, Dattatraya C.; Rajput, Parikshit K.; Kolekar, Sadhu K.; Late, Dattatray J.; More, Mahendra A.; Warule, Sambhaji S. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Herein, octahedron and stacked 2D hexagonal disc - like nanostructures of SnS2 were obtained by hydrothermal and ethylene glycol mediated hydrothermal methods, respectively. Attempt has been made to shade light on the plausible growth mechanism. Liquid phase exfoliation followed by centrifugation process leads to presence of tiny single crystalline SnS2 nanoparticles (similar to 5 nm) on the hexagonal discs over C substrate, characterized by preferred growth along {001} direction. The observed Raman shift and enhanced intensities of A(1g) and E-g modes infer charge interactions between the SnS2 disc and C substrate. Interestingly, the SnS2-C emitter exhibited superior field emission (FE) behaviour due to the unique morphology, excellent charge transfer, and reduced work function (similar to 4.1 eV). Here the extraction of large current density of similar to 1137 mu A/cm(2) at an applied field of 3.72 V/mu m, with good emission current stability. The present strategy is beneficial to design architectured morphology for multi-functionality.
Keywords: 2D layered materials; Field Emission (FE); SnS2; SnS2 on C

Electrocatalytic glycerol conversion: a low-voltage pathway to efficient carbon-negative green hydrogen and value-added chemical production - Chauhan, Inderjeet; Bajpai, Himanshu; Ray, Bishakha; Kolekar, Sadhu K.; Datar, Suwarna; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Applied Materials and Interfaces, 2024)
Electrochemical glycerol oxidation reaction (GLYOR) could be a promising way to use the abundantly available glycerol for production of value-added chemicals and fuels. Completely avoiding the oxygen evolution reaction (OER) with GLYOR is an evolving strategy to reduce the overall cell potential and generate value-added chemicals and fuels on both the anode and cathode. We demonstrate the morphology-controlled palladium nanocrystals, afforded by colloidal chemistry, and their established morphology-dependent GLYOR performance. Although it is known that controlling the morphology of an electrocatalyst can modulate the activity and selectivity of the products, still it is a relatively underexplored area for many reactions, including GLYOR. Among nanocube (Pd-NC), truncated octahedron (Pd-TO), spherical and polycrystalline (Pd-PC) morphologies, the Pd-NC electrocatalyst deposited on a Ni foam exhibits the highest glycerol conversion (85%) along with 42% glyceric acid selectivity at a low applied potential of 0.6 V (vs reversible hydrogen electrode (RHE)) in 0.1 M glycerol and 1 M KOH at ambient temperature. Owing to the much favorable thermodynamics of GLYOR on the Pd-NC surface, the assembled electrolyzer requires an electricity input of only similar to 3.7 kWh/m(3) of H-2 at a current density of 100 mA/cm(2), in contrast to the requirement of >= 5 kWh/m(3) of H-2 with an alkaline/PEM electrolyzer. Sustainability has been successfully demonstrated at 10 and 50 mA/cm(2) and up to 120 h with GLYOR in water and simulated seawater.
Keywords: electrocatalysis; Glycerol; green hydrogen; nanocube; Palladium; SDG